Estudo da técnica do balé clássico: uma comparação entre as escolas russa e inglesa - Araújo, Thays Emanuele Rocha de (2021)
Classical ballet is sought after not only by those who study dance, as it also serves as a basis for other segments of the artistic milieu. After being performed only by, and for royalty, ballet has broadly branched out into the world, giving rise to different ways of dancing and studying it. In view of this, seven ballet schools were conceived, and their respective methods, among all, two stand out for being more used in internationally renowned schools and companies, the Russian school and the English school. This investigation aims to gather data regarding the similarities and differences between these schools, with their respective methods, seeking to explain the implementation step by step, in order to record possible updates and information to demonstrate and compare positions, implementation steps, mentioning the specific terms and ways of doing. The description of certain steps was through observation of ballet classes in the city of Manaus - AM and references of authors who reported experiences with these methods as teachers or dancers, these records, which made it possible to enter the content taught, and in some of them, explanations of each level and the exercises studied.